The Effect of Unconventional Fiscal Policy on Consumption Expenditure - Francesco D'Acunto; Daniel Hoang; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2016)
Unconventional fiscal policy uses announcements of future increases in consumption taxes to generate inflation expectations and accelerate consumption expenditure. It is budget neutral and time consistent. We exploit a unique natural experiment for an empirical test of the effectiveness of unconventional fiscal policy. To comply with European Union law, the German government announced in November 2005 an unexpected 3-percentage-point increase in value-added tax (VAT), effective in 2007. The shock increased households' inflation expectations during 2006 and actual inflation in 2007. Germans' willingness to purchase durables increased by 34% after the shock, compared to before and to matched households in other European countries not exposed to the VAT shock. Income, wealth effects, or intratemporal substitution cannot explain these results.
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330; zero-lower bound; fiscal and monetary policy; durable consumption; survey data